2020
DOI: 10.1111/jfbc.13138
|View full text |Cite
|
Sign up to set email alerts
|

Royal jelly attenuates nonalcoholic fatty liver disease by inhibiting oxidative stress and regulating the expression of circadian genes in ovariectomized rats

Abstract: Nonalcoholic fatty liver disease (NAFLD) has a high incidence in postmenopausal women and is accompanied by insulin resistance, obesity, and dyslipidemia. Royal jelly (RJ), a natural substance derived from hive, possesses numerous health‐beneficial properties. Here, we evaluated the effects of RJ (150, 300, and 450 mg kg–1 day–1, 8 weeks) on NAFLD in ovariectomized (OVX) rats. Based on the results, RJ ameliorated the degree of anxiety, improved serum lipid profile, and attenuated the hepatic steatosis and live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
(77 reference statements)
2
12
0
Order By: Relevance
“…Yet, the mechanism by which RJ could exert its hypolipidemic, antioxidant, and anti-inflammatory effects is still not known. In previous research, the authors have shown the ability to increase the doses of RJ (150, 300, and 450 mg/kg) to alleviate NAFLD in rats and have attributed this to its antioxidant ability and regulation of circadian genes, including Per1 and Per 2, in the livers of ovariectomized rats [ 57 ]. In another study, the authors referred to the protective effect of RJ against NAFLD due to its antioxidant and anti-inflammatory effect, as well as regulating the metabolism of FAs such as α-linolenic acid, linoleic acid, arachidonic acid, and the biosynthesis of unsaturated fatty acids [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the mechanism by which RJ could exert its hypolipidemic, antioxidant, and anti-inflammatory effects is still not known. In previous research, the authors have shown the ability to increase the doses of RJ (150, 300, and 450 mg/kg) to alleviate NAFLD in rats and have attributed this to its antioxidant ability and regulation of circadian genes, including Per1 and Per 2, in the livers of ovariectomized rats [ 57 ]. In another study, the authors referred to the protective effect of RJ against NAFLD due to its antioxidant and anti-inflammatory effect, as well as regulating the metabolism of FAs such as α-linolenic acid, linoleic acid, arachidonic acid, and the biosynthesis of unsaturated fatty acids [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ovariectomy can cause estrogen deficiency in rats and is often used to develop an LLD model (22)(23)(24). After ovariectomy, body weight and FFA content were significantly higher in the model group than in the sham group (p, 0.05), and the accumulation of LD in liver cells was apparent, which suggests that the LLD model was successfully established in this study.…”
Section: Discussionmentioning
confidence: 58%
“…All these positive effects occurred due to the antioxidant effect of RJ and can be attributed to diverse biological mechanisms, among which the most important may be the capacity of RJ to increase the enzymatic activity of antioxidant enzymes specific to the liver, therefore reducing the levels of oxidative stress. The author’s discovery indicates that a potential natural treatment alternative for this liver disorder can be represented by RJ, by means of its strong antioxidant effect [ 116 ].…”
Section: Functional Properties Of Royal Jellymentioning
confidence: 99%